Thinking Disgust Plural (Itinera, 2017)
The paper explores the connections between disgust and contempt, arguing that contempt as a visceral and intellectual affect emerges out of a knowledge of disgust. Just as contempt can constitute a polished performance, so too disgusting objects can be transformed into art.Â